Ways to improve external structures for osteosynthesis of distal humerus fractures (early results) - Bodnya, A.; Dubovik, S. (Journal of Education, Health and Sport, 2020)
The results of the first clinical application of the developed external device for osteosynthesis of distal humerus fractures are presented. Purpose: to improve the extrafocal method of reposition and fixation of humerus shaft fractures at the level of the lower third, taking into account the anatomical and physiological features of the area damaged. Material and methods: Functional, basic fixing and repositioning capabilities of the previously used external device, its advantages and disadvantages are considered. A minimally invasive guided technique for external rod fixation in the treatment of low third humerus’ fractures is described. An improved version of the apparatus layout and transosseous osteosynthesis technology was used in 10 patients. The design of the device allows to eliminate the displacement of the humerus fragments, ensures the stability of their fixation, while maintaining the function of the elbow joint. The indications for the use of external fixation were extra-articular fractures of the humerus in the distal third - type 12A (n = 6), 12B (n =3) and 12C (n =1) according to the AO / ASIF classification. Results: The analysis of treatment outcomes showed that the technology of minimally invasive osteosynthesis allows to achieve positive results in most patients with a minimum of complications - 90.5 ± 3.3 points according to MEPS’s clinic method of assessing the function of the elbow joint. Conclusions: The developed device for transosseous osteosynthesis of distal humerus fractures, is the method of choice and can be widely used in traumatology and orthopedics.